Kenabian dan Rasionalitas dalam Perkembangan Peradaban - Mulyatno, Carolus Borromeus (Jurnal Orientasi Baru, 2012)
Is there any common points between the prophetic movement and rationality? There are three common things. First, prophetic movement and rationality reflect on life context. Secondly, they are transformative movements. Third, they lead to the developing of civilization that upholds the values of truth, justice and peace in the midst of the challenges of disintegration of nation and destruction of nature. In other words, they are an ethical movement. In the context of globalization characterized by life orientation on quantitative things, main role of prophecy and rationality is to restore the lives toward a wider horizon. They become relevant in our age when they actualize their role in solving humanitarian issues and promoting human civilization. For that prophetic movement requires a strong rational basis for networking and synergistic cooperation in developing a civilization of more qualified.